Fate or Folklore? Resolving Neptu-Based Marriage Conflicts Through Mediation in Dayu Village - Sholikah, Rahma Almatu (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the resolution of problematic neptu marriage in Dayu Village, Blitar Regency, where Javanese cultural traditions remain central to maintaining household harmony. In local belief, incompatible neptu combinations, numerological values derived from traditional Javanese calendars, can lead to persistent family conflict, misfortune, and even divorce. Using an empirical juridical method with an anthropological juridical approach, this research draws on interviews with ten key informants, including traditional and religious leaders, village officials, and community members. Secondary data were obtained from literature and legal sources. The findings reveal that neptu prohibitions are divided into two categories: absolute prohibitions, where certain weton combinations (e.g., Senin Wage–Selasa Legi, Jumat Legi–Selasa Legi) strictly forbid marriage, and conditional prohibitions, which permit marriage only after performing traditional rituals such as ruwatan, digauak-ditemu, and gembolan tujuh rupa. Crucially, the study demonstrates that the resolution of neptu conflicts aligns with the core principles of mediation philosophy, confidentiality, voluntariness, empowerment, neutrality, and unique solutions, particularly in cases of conditional prohibition. This reflects a culturally embedded form of facilitative mediation that emphasizes community-based conflict resolution. The study contributes to the discourse on indigenous conflict resolution by proposing a framework that integrates local customs with mediation theory. It offers valuable insights for scholars in anthropology, sociology, and legal studies, while promoting awareness of peaceful and sustainable approaches to family conflict rooted in local wisdom.